Description of Hypertension Sufferers on Elderly in Nursing Home Resident - Sembiring, Friska; Ginting, Amnita (Global Health Science Group, 2024)
Hypertension is one of the health problems in the world which is also referred to as the silent killer, Which is a deadly disease without any signs and symptoms beforehand as a warning of its dangers. The status of blood pressure will get higher as the function of the body's organs decreases. This type of research is quantitative descriptive. The sampling technique uses total sampling with a sample size of 30 people. The instrument used in the form of a tensimeter and blood pressure observation sheet.The results showed that the majority of respondents aged 60-74 years were 19 people (63.4%), the majority of respondents were female as many as 18 people (60%) and Blood pressure status in patients majority with hypertension grade 2 in Nursing Home Resident Medan is systolic blood pressure 140-159 mmHg, diastolic blood pressure 90-99 mmHg as many as 17 people (56.6%) It can be concluded that the majority of blood pressure status of hypertension sufferers on elderly in Panti werdha Graha Residen Senior Medan are in the category of Hypertension grade two.